Gender Disparity in Literacy in Unnao Tehsil, District Unnao - Gupta, Anushka; Sanyal, Srabani (National Geographical Journal of India, 2022)
Literacy is commonly taken as one of the stepping stones to development. It is often associated with probable higher educational attainment. Literacy in India is not poor but at the same time its progression is too slow. Additionally, the disparity that exists between the male and female is not a pretty picture to put forward. The present paper gives an account of the gender disparity in literacy through Gender Related Educational Development Index (GEDI) in Unnao tehsil using Census Data of 2011. The GEDI value for the tehsil varies from 0.251 to 0.876 with average standing at 0.699 but it is 0.6355 for the rural and 0.8028 for urban areas.Innumerable government initiatives have encouraged education and skill development of the population irrespective of gender, but the results received are not as expected. The spatial disparity of the values indicate insufficient diffusion of awareness and resources in the area in addition to varies sociocultural factors that play an important role in women’s upliftment